Teacher Ability to Apply Questioning Skills in Elementary School - Putri, Milennia Liza; Dafit, Febrina (Universitas Pendidikan Ganesha, 2022)
In the learning process, the teacher dominates learning with the lecture method, acting as the primary source so that students are only listeners and recipients. Students do not participate actively in the learning process. Students should be involved in the learning process to meaningful learning for students. One way to include students in the learning process is by asking students. The purpose of this study is to examine how the ability of teachers to apply questioning skills in elementary schools, whether teachers can build questioning skills well or not. The approach used in this research is descriptive qualitative. The research subjects found five classroom teachers. They collected data through observation and interviews, namely aspects of observation and interview questions based on the components of basic questioning skills and advanced questioning skills. The data analysis used is the concept of Miles and Huberman with the stages of data reduction, data presentation and verification. The research results were teachers mastered questioning skills quite well, but they were not optimal in further questioning skills. Questioning skills are essential because this can increase students' motivation and interest in learning to become more active and develop students' critical and creative thinking skills. Teachers should need to re-learn the components of questioning skills to have a better influence on the learning that students receive.